Finite Element Simulation of the Deformation of a Cell Driven by Creeping Flow - Serrano Alcalde, F.; García-Aznar, J.M.; Gómez Benito, MJ (Jornada de Jóvenes Investigadores del I3A, 2017)
The purpose of this work is to calculate the deformation undergone by a cell in function of its nucleus size and mechanical properties. The cell immersed in a fluid go through a variable section channel and it is deformed by fluid forces. Cell deformation into the channel causes changes at the fluid velocity profile. This fluid configuration change results in diferent normal and viscous forces around the cell. Due to strong correlation between cell deformation and fluid velocity profile, a fluidsolid interacción (FSI) is required.